Thursday

April 17, 2014

April 17, 2014

Posted by **Alicia** on Sunday, November 18, 2007 at 9:26pm.

- College Algebra -
**Reiny**, Sunday, November 18, 2007 at 10:15pmmatch

2x^2 - 3x - 2 = 0 with

ax^2 + bx + c = 0

so a=2, b=-3, c=-2

the formula says

x = (-b ±√(b^2 - 4ac))/(2a)

substitute the above values and simplify

(did you get x=2, x=-1/2 ?)

**Related Questions**

Algebra - i need to use the quadratic formula 2 solve these 4 questions: 1. x(...

algebra - solve by using the quadratic formula prove your answer is correct by ...

algebra - Use the quadratic formula to solve the equation. -4x^2-3x+2=0 Can ...

algebra - Solve the quadratic equation: 2x(squared)+6x+12=0 I know you have to ...

College Math II - Solve by using the quadratic formula. x^2 + 6x + 6 = 0 I am ...

Math - Using the quadratic formula solve xsquared=2/3x Using the quadratic ...

ALGEBRA - what does it mean to state the solution in the problem if the equation...

Math!Please Help Me! - Solve the following quadratic by either factoring or ...

Algebra - can show me how to do this with out just squaring 3x^(1/2) - x - 6 = 0...

quadratic equations - can you solve the equation using the quadratic formula x2...